Blue economy of the Indian Ocean : resource economics, strategic vision, and ethical governance - Mukhopadhyay, Ranadhir; Loveson, V. J., 1962-; Iyer, Sridhar D.; Sudarsan, P. K. (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
The economic paradigms currently dominating the world are not sustainable. The threats from climate change, exploitation-based approaches to commerce, and the excess acquisition of resources loom large as well as the possibility of military flare-ups. Maintaining a balance between development and ecosystems, aspirations for growth, and the need for sustainability is a prescient challenge. The Indian Ocean Region (IOR) encompasses some of the poorest countries in the world and those that will bear the brunt of the negative impacts from climate change. This book explores the immense potential of the IOR and how best to maintain sustainable and responsible economic and strategic activities. The combination of science, innovation, and entrepreneurship will create a new blue economy business model, which has the potential to transform society. Based on critical analysis of the model and its practical applications, including risks as well as opportunities, the topics discussed range from food security, energy, and resilience to climate change, trade and investments, and improved maritime connectivity to tourism, poverty alleviation, and socioeconomic growth, encompassing a wide range of interests and expertise. FEATURES Examines the geo-politics, geo-resources, and geo-hazards of the IOR and identifies opportunities and methods to achieve success Covers a detailed assessment of available resources (fisheries, minerals, energy), threats such as pollution (plastic, acoustic, carbon, bio-invasion), geo-politics (maritime security, military invasion), and strategic vision (determining carrying capacity, ethical governance, and responsible ecosystem) of the Indian Ocean Analyzes the economics of the blue economy, the global scenario including the Pacific and Caribbean islands, and the aspect of the Chinese geo-political invasion in the Indian Ocean Inspires entrepreneurs to adopt new ways of creating economic benefits, reducing energy use, and increasing revenue while simultaneously helping the communities involved Discusses the threat and security perspectives of the IOR and the collective responsibility for a sustainable use of resources Crossing a wide range of interests and expertise, this book explores topics and ideas that will be essential to researchers and professionals in marine sciences, economics, business, geography, and political sciences. Graduate students in the same fields as well as any and all organizations that maintain a presence in the IOR will likewise find this book to be a valuable resource.
4.2 United States of America -- 4.2.1 Blue Economy Activities -- 4.2.2 Marine Environment Conservation Policy -- 4.3 Japan -- 4.3.1 Blue Economy Activities -- 4.3.2 Marine Environment -- 4.4 Canada -- 4.4.1 Blue Economy Activities -- 4.4.2 Marine Environment and Conservation Policy -- 4.5 New Zealand -- 4.5.1 Blue Economy Activities -- 4.5.2 Marine Environment and Conservation Policy -- 4.6 Brazil -- 4.6.1 Blue Economy Activities -- 4.6.2 Marine Environment and Conservation Policy -- 4.7 Pacific Islands -- 4.7.1 Fiji -- 4.7.1.1 Blue Economy Activities
4.7.1.2 Marine Environment and Conservation Policy.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Indian Ocean Region; Indian Ocean Region -- Economic conditions; SCIENCE / Earth Sciences / Oceanography; BUSINESS & ECONOMICS / Environmental Economics; NATURE / Environmental Conservation & Protection